The effects of platelet-rich plasma injections in different stages of knee osteoarthritis - Annaniemi Juho A; Pere Jüri; Giordano Salvatore (France, 2025)
Purpose: Platelet-rich plasma (PRP) injections are challenging the current treatment options for knee osteoarthritis (KOA). Targeting the treatment to optimal stage of the symptomatic KOA may be crucial in the success and failure of treatment. The aim of this study is to compare the outcomes of PRP injections at different stages of KOA in order to determine the optimal stage of the KOA for PRP injection treatments.
Methods: A total of 89 consecutive patients with symptomatic KOA Kellgren-Lawrence grade 1 to 3 (Group A grade 1, group B grade 2 and group C grade 3) were given three intra-articular injections of PRP with 2 weeks interval between injections. Visual Analogue Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Range of Motion were measured before injection, at 15 days, 6 months, 12 months and, at last follow-up. Intergroup outcomes were compared.
Results: The comparison of groups A and C showed that WOMAC scores were significantly higher in group C at 15 days [p = 0.047] and at last follow-up [p = 0.008] than in group A, as well as VAS scores at 6 months [p = 0.031] and at last follow-up [p = 0.008]. The overall WOMAC and VAS scores showed decrease in all the groups in minimum follow-up of 14 months. The other comparisons did not show significant differences in outcomes.
Conclusion: All the groups showed decrease in WOMAC and VAS, but patients with mild KOA benefit significantly more from the treatments than patients with more severe KOA.